Enterprise risk management : from incentives to controls - Lam, James (Hoboken, New Jersey : Wiley, 2014)
'A fully revised second edition focused on the best practices of enterprise risk managementSince the first edition of Enterprise Risk Management: From Incentives to Controls was published a decade ago, much has changed in the worlds of business and finance. That's why James Lam has returned with a new edition of this essential guide. Written to reflect today's dynamic market conditions, the Second Edition of Enterprise Risk Management: From Incentives to Controls clearly puts this discipline in perspective.Engaging and informative, it skillfully examines both the art as well as the science of effective enterprise risk management practices. Along the way, it addresses the key concepts, processes, and tools underlying risk management, and lays out clear strategies to manage what is often a highly complex issue. Offers in-depth insights, practical advice, and real-world case studies that explore the various aspects of ERM Based on risk management expert James Lam's thirty years of experience in this field Discusses how a company should strive for balance between risk and return Failure to properly manage risk continues to plague corporations around the world. Don't let it hurt your organization. Pick up the Second Edition of Enterprise Risk Management: From Incentives to Controls and learn how to meet the enterprise-wide risk management challenge head on, and succeed'--
Section One. Risk Mangement in Context -- ch. 1 Introduction -- The Benefits of Risk Management -- Integration Adds Value -- Cautionary Tales -- ch. 2 Lessons Learned -- Lesson #1 Know Your Business -- Lesson #2 Establish Checks and Balances -- Lesson #3 Set Limits and Boundaries -- Lesson #4 Keep Your Eye on the Cash -- Lesson #5 Use the Right Yardstick -- Lesson #6 Pay for the Performance You Want -- Lesson #7 Balance the Yin and the Yang -- ch. 3 Concepts and Processes -- Risk Concepts -- Risk Processes -- Risk Awareness -- Risk Measurement -- Risk Control -- Risk Is a Bell Curve -- ch. 4 What Is ERM? -- ERM Definitions -- The Benefits of ERM -- The Chief Risk Officer -- Components of ERM -- Section Two. The Enterprise Risk Management Framework -- ch. 5 Corporate Governance -- Codes of Conduct -- Best Practices -- Linking Corporate Governance and ERM -- ch. 6 Line Management -- The Relationship Between Line and Risk Functions -- Key Challenges -- Best Practices -- ch. 7 Portfolio Management -- The Theory of Active Portfolio Management -- Benefits of Active Portfolio Management -- Practical Applications of Portfolio Management -- ch. 8 Risk Transfer -- A Brief History of ART -- Advantages of ART -- Pitfalls of ART -- A Look to the Future -- Case Study: Honeywell -- Case Study: Barclays -- ch. 9 Risk Analytics -- Risk Control Analytics -- Risk Optimization Analytics -- Market Risk Analytics -- Credit Risk Analytics -- Credit Portfolio Models -- Operational Risk Analytics -- GRC Systems -- ch. 10 Data and Technology -- Early Systems -- Data Management -- Interface Building -- Middleware -- Distributed Architectures -- Key Factors for a Successful Implementation -- ch. 11 Stakeholder Management -- Employees -- Customers -- Regulators -- Rating Agencies -- Shareholder Service Providers -- Business Partners -- Section Three. Risk Management Applications -- ch. 12 Credit Risk Management -- Key Credit Risk Concepts -- The Credit Risk Management Process -- Basel Requirements -- Best Practices in Credit Risk Management -- Case Study: Export Development Corporation (EDC) -- ch. 18 Market Risk Management -- Types of Market Risk -- Market Risk Measurement -- Market Risk Management -- Best Practices in Market Risk Management -- Case Study: Market Risk Management at Chase -- ch. 14 Operational Risk Management -- Operational Risk---Definition and Scope -- The Operational Risk Management Process -- Best Practice in Operational Risk Management -- Emerging IT Risks -- Case Study: Heller Financial -- ch. 15 Business Applications -- Stage I Minimizing the Downside -- Stage II Managing Uncertainty -- Stage III Performance Optimization -- The Further Evolution of Risk Management -- ch. 16 Financial Institutions -- Industry Trends -- Risk Management Requirements -- Systemic Risk -- A Look to the Future -- Case Study: CIBC -- ch. 17 Energy Firms -- Industry Trends -- Risk Management Requirements -- A Look to the Future -- Lessons Learned from Enron -- Lessons Learned from the BP Oil Spill -- ch. 18 Non-Financial Corporations -- Risk Management Requirements -- Best Practices in Corporate Risk Management -- Case Study: Microsoft -- Case Study: Ford -- Case Study: Airbus and Boeing -- Section Four. A Look to the Future -- ch. 19 Predictions -- The Profession of Risk Management -- Technology and the Convergence of Risk Management -- Ten Predictions -- 2013 Looking Back -- ch. 20 Everlast Financial -- Section Five. ERM Implementation -- ch. 21 ERM Implementation -- Benefits of Corporate Governance and ERM Practices -- ERM Implementation Requirements -- ERM Maturity Model -- Other ERM Maturity Models -- Risk Culture -- ch. 22 Role of the Board -- Board Oversight Requirements -- Current Board Practices -- Case Study: JP Morgan Chase -- The Last Line of Defense -- ch. 23 Risk Assessment -- Risk Assessment Methodology -- Best Practice Case Studies in Risk -- Appendix: Risk Assessment Self-Evaluation Checklist -- ch. 24 Risk-Based Decision Making -- ERM Decisions and Actions -- Creating Value through ERM -- Case Study: Duke Energy -- ch. 25 Dashboard Reporting -- Traditional versus Dashboard Reporting -- General Dashboard Applications -- ERM Dashboard Implementation -- Evolving Best Practices.
Includes bibliographical references (pages 451-464) and index.
Keywords: Risk management